Mathematical-cartographic modeling of density of building of urban environment - Makarova K.P.; Levina Yu.S.; Zarubin O.A.; Klimov A.E. (Научно-технический вестник Брянского государственного университета)
The article is devoted to the problems of mathematical-cartographic modeling of the density of building as the most important indicator of urban planning. The research was conducted on the example of the territory of Proletarsky area of the city district of Saransk. Modeling is performed in the ArcGIS 10.0 based on the created electronic layers and spatial databases. Characteristics of the housing stock of Proletarsky area of the city district of Saransk was used as a statistical data. The map of the functional zones of the General Plan of the city district of Saransk and the geoimage from the Yandex.Maps service (the SAS.Planet program) served as the initial map data. The projection of Gauss Kruger, coordinate system SK-42 was used for the projected maps. The density map of the Proletarsky area of the city district of Saransk was obtained as a result of the implementation of the stages of mathematical and cartographic modeling. An experimental research was conducted on the choice of the most optimal cell size for a regular grid when constructing a cartographic model. The compliance of the density of the building of the Proletarsky area with normative indicators was revealed by the authors.